SISTEM INFORMASI TRANSAKSI PENJUALAN OBAT BERBASIS WEBSITE MENGGUNAKAN METODE PROTOTYPE - Khikmatul Maulidah; Hendri Ardiansyah (CV. Multi Kreasi Media, 2024)
A pharmacy is a place to mix and sell medicines based on doctor's prescriptions and sell medical items. This pharmacy is usually used for the benefit of the community to help people obtain medicines that are most likely to be unwell or sick. Pharmacy as a means of health services that must prioritize the interests of community customers and function to store, provide, deliver quality medical devices and pharmaceutical supplies. One of them is Hazmi Farma Pharmacy which is located on jl. Raya Kalipucang, Brebes, Central Java, with pharmacy license number 440.1/22/DPMPTSP, is a clinic that provides health services and sells various kinds of medicines to the public based on doctor's prescriptions or without prescriptions from doctors. So far, the management of drug sales transactions at Hazmi Farma Pharmacy is still done manually, namely transaction data is still handwritten in a ledger and then stored on document storage shelves. So from these problems there is difficulty finding records of drug sales transactions and loss of records of drug sales transactions needed and pharmacies have to provide more space for general ledger storage. Referring to this background, research will be carried out on